The Influence of Using Poetry Musicalization Model Local Wisdom Themed on Writing and Reading Poetry Skills in Elementary School - Prawiyogi, Anggy Giri; Rahman; Sastromiharjo, Andoyo (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to describe the influence of using poetry musicalization model local wisdom themed on writing and reading poetry skills in elementary schools. This research is quantitative research with experimental design in grade 5th SDIT Cendikia Purwakarta. The use of this model is expected to have an impact on the quality of poetry learning with indicators of increasing students’ writing and poetry reading skills. The musical model of poetry in this research is the use of both modern and traditional music technology to accompany poetry readings and giving tones in the poetry verse so that children’s poetry can be sung. The theme of local wisdom used is Purwakarta’s local wisdom in the form of places that have local wisdom in the Purwakarta area that can inspire children to write poetry. The results showed that the use of poetry musicalization model can significantly improve the quality of poetry learning in elementary schools. This can be seen in the results of the assessment of children’s writing and poetry reading skills before and after the use of this model. The use of a poetry musicalization model with the theme of local wisdom encourages student enthusiasm in learning so that students’ writing poetry and reading skills also increase. Students’ childhood experiences related to Purwakarta’s place of local wisdom inspire and enrich their vocabularies. This makes it easier for students to choose diction in writing poetry. In addition, children tend to like music and singing so they are challenged to be able to create something from what they write. Thus the use of a musical model with the theme of wisdom looks effective for poetry learning in elementary schools in the 21st-century education era that emphasizes a wright with technological involvement without forgetting the wealth of local wisdom of students.